On the non-distinction of self and other in the notion of personhood - Sta. Maria, Madelene A. (Animo Repository, 2008)
Chaudhary's (2008) analysis is viewed as compatible with recent findings in the neurosciences that the experience of personhood cannot be limited to "cold" individual rationality and "pure" monologic cognition. The search for, and evaluation of-- other minds is neurologically enabled. Chaudhary's account of the dialogical self in Indian families as unavoidably relational and naturally sensitive to others seems to be the logical outcome of a neurobiological "circuit" for empathy.